2016
DOI: 10.3389/fpsyg.2016.01071
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Ethnic Classroom Composition and Turkish-Origin and German Students' Reading Performance and Sense of Belonging

Abstract: Past research on ethnic composition effects on migrant and ethnic majority students' performance has reported inconclusive results: Some studies have found no relationship between the proportion of migrant students in school and students' performance, some revealed positive effects, whereas others showed negative effects of the proportion of migrant students. Most of the studies did not consider whether an increase in the proportion of migrant students in the classroom has different effects on migrant and ethn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 66 publications
(91 reference statements)
1
14
0
1
Order By: Relevance
“…The following lines of research suggest that the sense of belonging to a university can be undermined by experiencing a low fit between one's own self‐construal and the perceived norm of the university, whereas experiencing a high fit should bolster this sense of belonging. According to a study by Mok et al (2016), for instance, the sense of belonging of high school students with a minority background depends on their fit with the norms in their class. Moreover, research has repeatedly shown that P‐E fit correlates with organizational identification, satisfaction with the supervisor and colleagues, as well as group cohesion (for a meta‐analysis see Kristof‐Brown et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The following lines of research suggest that the sense of belonging to a university can be undermined by experiencing a low fit between one's own self‐construal and the perceived norm of the university, whereas experiencing a high fit should bolster this sense of belonging. According to a study by Mok et al (2016), for instance, the sense of belonging of high school students with a minority background depends on their fit with the norms in their class. Moreover, research has repeatedly shown that P‐E fit correlates with organizational identification, satisfaction with the supervisor and colleagues, as well as group cohesion (for a meta‐analysis see Kristof‐Brown et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…For immigrant background factors, immigrant students perform consistently worse than native students (e.g., Liberto, 2014), which can be explained by insufficient family support and the control of immigrants (Santos et al, 2016). In the meantime, it has also been found that the sense of school belonging exerts a moderating effect in the mathematical achievement gap between immigrants and natives (Schachner et al, 2017); however, for reading performance, this moderating effect turns out to be insignificant (Mok et al, 2016). The second category is related to cognitive factors.…”
Section: Introductionmentioning
confidence: 99%
“…German students do not suffer when they are in classrooms with a high proportion of (lowerperforming) Turkish-origin students (e.g., Mok et al, 2016), which also speaks for an VERTICAL COLLECTIVISM AND STEREOTYPE THREAT 24 implementation of ethnically mixed and ability-related grouping during collaborations in the classroom. However, more research is needed to explore these effects.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Today, children of Turkish-origin migrants perform more poorly in standardized tests than Germans and other migrant groups (e.g., Bos, 2012;Klieme et al, 2010;Mok, Martiny, Gleibs, Keller, & Froehlich, 2016) and are less likely to attain higher education (e.g., Kristen, Reimer, & Kogan, 2008). On the one hand this underperformance is surprising, because research shows that the Turkish culture strongly values achievement motivation (e.g., Phalet & Claeys, 1993;Verkuyten, Thijs, & Canatan 2001), and high achievement motivation and good performance outcomes are expected from Turkish students by their families (Phalet & Claeys, 1993).…”
mentioning
confidence: 99%